Case report: Multidrug-resistant Streptococcus pseudoporcinus isolated from an infected surgical wound of a 9-year-old spayed female Great Dane dog - Soku, Yesutor K.; Etzioni, Athema L.; Mohamed, Abdelrahman (Frontiers in Veterinary Science, 2023)
Streptococcus pseudoporcinus (S. pseudoporcinus) is a β-hemolytic, Gram-positive novel bacterium first identified in 2006. It is a catalase-negative, non-motile coccus arranged in short chains. Furthermore, it has a broad beta-hemolytic reaction on sheep blood agar and cross-reacts with Lancefield group B antigen agglutination reagent. In this study, we report a case of S. pseudoporcinus infection of a surgical wound on the left metatarsus of a dog. The patient is a 9-year-old spayed female Great Dane dog with a brief history of multiple cutaneous masses being removed. Post-surgery, the post-surgical site on the left metatarsus became infected and discharged purulent material with a fetid odor. Upon preliminary diagnostic testing, we detected catalase-negative Gram-positive cocci exhibiting beta-hemolytic growth on sheep blood agar. A VITEK® 2 Compact machine from bioMérieux identified the bacterium as S. pseudoporcinus. Furthermore, antibiotic testing revealed multidrug resistance. Therefore, we document a multidrug-resistant S. pseudoporcinus isolate as a cause of canine post-surgical wound infection. Furthermore, it was the only isolate detected from the sample; hence, it is the cause of the infection. To our knowledge, this case is the first report of S. pseudoporcinus in a dog.